Unemployment Challenges in Nigeria: The Imperative for Economic Diversification - Abdulrazaq , Bashir Oladimeji; Lambe, Emmanuel Oyewole (Kashere Journal of Politics and International Relations, 2024)
This study delves into the complex issues surrounding unemployment in Nigeria, specifically examining the challenges faced by the agricultural sector and the youth population in embracing innovative technologies. Nigeria currently grapples with a severe economic crisis marked by political instability, volatile markets, and escalating unemployment. Amidst these challenges, the nation stands at a pivotal juncture for transformative change, with agriculture and manufacturing emerging as key focal points for revitalization. The agricultural sector, once the backbone of Nigeria's economy, encounters obstacles ranging from outdated practices to limited access to modern technologies. Simultaneously, the country's youth, harboring untapped potential in technological innovation, face barriers like inadequate education and restricted resources, impeding their entrepreneurial pursuits and worsening unemployment. The paper adopts the use of qualitative secondary materials. The theoretical framework of this research is anchored in the theory of empowerment, providing a robust foundation for comprehending and addressing the unemployment challenge in Nigeria through the adoption of the diversification imperative in agriculture and manufacturing. The theory of empowerment underscores the significance of empowering individuals, particularly youths, through active participation in entrepreneurial activities, enhancing their decision-making abilities and acquiring crucial skills. The research was able to find out that the inability of the government to diversify the economy since the oil discovery and boom period serves as the problem fueling unemployment. This research recommends the adoption of economic diversification in agriculture and manufacturing as a strategic imperative to forge a prosperous future.